INTERNAL GOVERNANCE MONITORING AND EARNINGS QUALITY - RUSMIN RUSMIN (Jurnal Bisnis dan Akuntansi, 2011)
This study examines the earnings quality of the Indonesian manufacturing listed firms for years 2003 to 2009. Statistical analysis reveals that size of board and board commissioner independence help predict the quality of financial information. A large number of board commissioner members relates with higher earnings quality. Moreover, the presence of the independent board of commissioners associates with higher financial reporting quality. Interestingly, audit committee attributes especially percentage of independent members on the audit committee and number of audit committee member are not significant predictors. This has significant implications for Indonesian companies since globally companies are moving towards a more regimented corporate governance structure to enhance firm performance.